A qualitative evaluation to explore the suitability, feasibility and acceptability of using a ‘celebration card’ intervention in primary care to improve the uptake of childhood vaccinations - Lwembe,SC; Green,SA; Tanna,N; Connor,J; Valler,C; Barnes,R (BMC Family Practice, 2016)
IntroductionChildhood vaccination remains a primary mechanism for reducing the burden of infectiousdisease. In the United Kingdom, as in many countries, a sustained effort is required to ensurethat vaccination targets are met to afford protection to the whole population from vaccinepreventable disease. The Celebrate and Protect programme is a collaborative partnershipdeveloped to improve the uptake of childhood vaccination across a number of boroughswithin London through the use of a celebration card to encourage attendance for vaccinationand enhance relationships between general practices and the parents/carers of children.MethodsThis study was undertaken to assess the suitability, feasibility and acceptability of theCelebrate and Protect programme across nine boroughs in London. Data were collectedeither from telephone interviews (n=24) or from focus groups (n=31). A total of 55 keyinformants were included in the study, representing strategic, commissioning or policy leads,healthcare professionals and primary care teams delivering vaccinations and parents/carersof children under five.ResultsThe analysis of data identified that whilst parents/carers saw the celebration card positivelythis raised the issue of ‘vaccine hesitancy’ and the lack of information that parents/carershave to make informed decisions about vaccination. Similarly, healthcare professionalsviewed the programme positively and felt that it was deliverable within existing resourcesalthough they raised wider questions about on-going sustainability and about quantitativedata collection. In relation to the collaboration between primary care and a pharmaceuticalcompany in developing the Celebrate and Protect programme, it was generally felt that,provided appropriate governance is in place, it was a pragmatic approach in which thebenefits outweighed any perceived disadvantages.DiscussionThe Celebrate and Protect programme was seen as an innovative collaborative programmeto engage with parents